Epistemologi Kesetaraan Gender di Indonesia dalam Konteks Islam dan Strukturasi Sosial Perspektif Mufidah Cholil - Fitria, Fitria; Ningsih, May Lita Wardiya (MAN 4 Kota Pekanbaru, 2024)
This study explores the issue of gender equality from Mufidah Cholil's perspective with a sociological approach, structural theory, and social construction. Through content analysis, writers explore Mufidah's thoughts on the issue of gender equality in her book “Bingkai Sosial Gender”. This study's findings revealed that Mufidah employs a sociological approach to describe the gender equality issue with regards to socio-cultural background and Islamic views. She shows on how gender discourse has developed in Indonesian society and emphasizes that it is not an absolute truth, rather it is a concept that is constructed by society. Mufidah also integrates the Islamic perspective with structuration theory and social construction to provide a holistic solution towards gender issues. This study's significance lies in the policy formulation and strategic approach to achieve gender equality.